Derivation of water quality criteria of zinc to protect aquatic life in Taihu Lake and the associated risk assessment. (15th October 2021) - Li, Lu; He, Yanjiao; Song, Kang; Xie, Fazhi; Li, Huixian; Sun, Fuhong
Abstract: Zinc is a widely distributed environmental pollutants and has been listed as priority heavy metal pollutant in China. Similar as other heavy metals, toxicity of zinc to aquatic organisms affects by environmental factors such as water hardness. It is necessary to develop regional water quality criteria (WQC) to protect native aquatic life against zinc due to the diversity of aquatic organisms' variability across different water systems, as a concretization and supplement for national zinc WQC. This study derived WQC for zinc by species sensitivity distribution (SSD) curve method. The zinc toxicity data of the aquatic organisms in Taihu Lake used in SSD curve was collected based on published toxicity data for zinc with hardness values and supplemented with acute toxicity tests conducted in this study. Six aquatic organism natives to Taihu Lake were selected to conduct zinc acute toxicity test in a range of hardness conditions. The relationship between water hardness and zinc toxicity was constructed. The criterion maximum concentration (CMC) and criterion continuous concentration (CCC) for zinc in Taihu Lake were then derived, which considered the water quality and taxonomic groups in Taihu Lake. The CMC and CCC were 100.69 μg/L and 30.79 μg/L, respectively. The environmental risk of zinc to Taihu Lake are acceptable, at moderate to low levels. This study has provided a basis for regional water quality criterion derivation and risk assessment in China. Graphical abstract: Image 1 Highlights: Acute toxicity of zinc to aquatic organisms in Taihu Lake was investigated. Acute toxicity of zinc reduces with the increasing of water hardness. The criterion maximum concentration of zinc for Taihu lake is 100.69 μg/L. The criterion continuous concentration of zinc for Taihu Lake is 30.79 μg/L. The environmental risk of zinc to Taihu Lake are at moderate to low levels.